ANIMAL MODELS AS AN EXPERIMENTAL TOOL IN DIABETES RESEARCH - Tamma, Navin Kumar (Journal of Drug Delivery and Therapeutics, 2013)
The review give an overview on the animal models, their short comings and the precautions required for each technique to the investigators in diabetes research. Data was collected from journals,electronic library, standard text books of experimental pharmacology analysed and relevant data was taken The disease remains incurable and can be only controlled by discovering new drugs choosing various experimental diabetes models to minimise the risk of diabetic complications.